Wilhelmsburg is our home! : racialized residents on urban development and social mix planning in a Hamburg neighbourhood - Chamberlain, Julie (Urban studies (Bielefeld, Germany), 2022)
In a neighbourhood facing massive redevelopment, racialized residents speak about stigma, social mixing, and what the island community means to them. Based on rich interviews, photographs, and archival research, Julie Chamberlain rejects the usual silence in German urban studies around racialization and examines how constructing some groups as "not belonging" has shaped Hamburg-Wilhelmsburg's past and present. For racialized long-time residents, it is Heimat, a space of belonging in the context of exclusion. As social mix policy threatens that belonging, residents explore their hopes and their fears for the future of an urban space where gentrification looms.